Children’s Quality and Quantity in Nigeria: A Granger Causality Analysis - K. A., Olabiyi; O.O., Awe (Humaniora, 2017)
This research investigated the cointegration and causal relationships between children’s quality and quantity in Nigeria. The research was based on secondary data obtained from the World Development Indicator database (1980-2014), United Nations Statistics Division's Statistical Yearbook, and the UNESCO Institute for statistics online database. Children’s quality denoted by the education of the child was proxied by government education expenditure and life expectancy rate, while the quantity of the children denoted by the size of the family was proxied by total fertility rate, infant mortality rate, and the adolescent fertility rate. For analysis, Augmented Dickey Fuller unit root test, Johansen-Juselius cointegration analysis, and Granger causality tests were conducted. Johansen-Juselius cointegration test results indicate that there is a long-term relationship among the selected variables. Meanwhile, the Granger causality test shows that the causation between the quality and quantity of children is both unidirectional and bi-directional depending on the variable of the quantity of children. The quantity of the children is the cause in the unidirectional causation. Furthermore, a trade-off is established between the quality and quantity of children. Therefore, the policies of the government in encouraging and promoting the reduction of the rate of fertility should be pursued further for an increased level of education of the child.